Advances in radiation therapy - Guckenberger, Matthias 1976-; Combs, Stephanie Elisabeth 1976-; Zips, Daniel 1970- (Progress in tumor research / series editors Rolf A. Stahel, Solange Peters, 2018)
Developments in radiation oncology have been key to the tremendous progress made in the field in recent years. The combination of optimal systemic treatment and local therapy has resulted in continuing improved outcomes of cancer therapy. This progress forms the basis for current pre-clinical and clinical research which will strengthen the position of radiation oncology as an essential component of oncological care. This book summarizes recent advances in radiotherapy research and clinical patient care. Topics include radiobiology, radiotherapy technology, and particle therapy. Chapters cover a summary and analysis of recent developments in the search for biomarkers for precision radiotherapy, novel imaging possibilities and treatment planning, and advances in understanding the differences between photon and particle radiotherapy. Advances in Radiation Therapy is an invaluable source of information for scientists and clinicians working in the field of radiation oncology. It is also a relevant resource for those interested in the broad topic of radiotherapy in general.